Some rise by sin : a novel - Caputo, Philip (Henry Holt and Company, 2017)
"The Mexican village of San Patricio is being menaced by a bizarre, cultish drug cartel infamous for its brutality. As the townspeople try to defend themselves by forming a vigilante group, the Mexican army and police have their own ways of fighting back. Into this volatile mix of forces for good and evil (and sometimes both) steps an unlikely broker for peace: Timothy Riordan, an American missionary priest who must decide whether to betray his vows to stop the unspeakable violence and help the people he has pledged to protect. Riordan's fellow expatriate Lisette Moreno serves the region in a different way, as a doctor who makes "house calls" to impoverished settlements, advocating modern medicine to a traditional society wary of outsiders. To gain acceptance, she must keep secret her rocky love affair with artist Pamela Childress, whose troubled emotions lead Moreno to question their relationship. Together, Lisette and Riordan tend to their community. But when Riordan oversteps the bounds of his position, his personal crisis echoes the impossible choices facing a nation beset by instability and bloodshed."--Amazon.com